Intelligent Scheduling of Robotic Flexible Assembly Cells - Abd, Khalid Karam; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book focuses on the design of Robotic Flexible Assembly Cell (RFAC) with multi-robots. Its main contribution consists of a new effective strategy for scheduling RFAC in a multi-product assembly environment, in which dynamic status and multi-objective optimization problems occur. The developed strategy, which is based on a combination of advanced solution approaches such as simulation, fuzzy logic, system modeling and the Taguchi optimization method, fills an important knowledge gap in the current literature and paves the way for future research towards the goal of employing flexible assembly systems as effectively as possible despite the complexity of their scheduling.
Keywords: Computational intelligence; Manufactures; Control engineering; Robotics; Automation; Artificial intelligence; Computational Intelligence; Machines, Tools, Processes; Control, Robotics, Automation; Artificial Intelligence